2012
DOI: 10.1637/9910-083111-case.1
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Unilateral Periorbital Cellulitis and Mandibular Osteomyelitis in a Turkey Flock

Abstract: A farm of meat turkeys was affected by a condition, clinically characterized by unilateral inflammation of the orbital region and progressive crossing of the beak, observed in three successive flocks in 2010. While no toxic, genetic, technical, or diet causes could be found, pathologic and bacteriologic analyses were conducted to investigate the case. Pathologic analyses of the heads of affected birds showed blepharitis and exudative sinusitis as well as severe chronic osteomyelitis of all skull bones and mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Both coagulase-positive, especially S. aureus, and coagulasenegative Staphylococcus spp. (CoNS) has been implicated as an etiological agent in many avian pathologies (Corrand et al, 2012). The clinical signs most associated with Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Both coagulase-positive, especially S. aureus, and coagulasenegative Staphylococcus spp. (CoNS) has been implicated as an etiological agent in many avian pathologies (Corrand et al, 2012). The clinical signs most associated with Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies focusing on the presence of methicillin-resistant S. aureus (MRSA) carriage among turkeys (Richter et al, 2012) and turkey meat products (de Boer et al, 2009;Feßler et al, 2011a) have been published. However there is little research on S. aureus involved in disease in turkeys, with the exception of osteomyelitis cases (Alfonso & Barnes, 2006;Corrand et al, 2012). Recently, German results showed that livestock-associated MRSA may represent a larger cause of human infection than estimated previously (Köck et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopic lesions in brain tissues following the injection of partridges were mostly inapparent, but the histopathological examination of the brain tissue revealed congestion and thrombosis. Experimentally induced staphylococcosis as well as naturally occurring disease have been reported in chickens (Mutalib et al 1983a, McNamee et al 2000, Jiang et al 2015, turkeys (Linares et al 2001, Corrand et al 2012, pet birds (Briscoe et al 2008, Huynh et al 2014, Iverson et al 2015, birds of prey (Poorbaghi et al 2012, Bezjian 2014, waterfowl (Degernes et al 2011, Mondal et al 2014, and other avian species (Lemon et al 2012). The pathogenesis of systemic infection with Staphylococcus aureus in chukar partridge chicks is not clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Infection can occur in birds following a breakdown in the natural defense mechanisms of the host such as a skin wound or inflamed mucous membrane. The open navel of newly hatched chicks, vaccinations and beak or toe trimming, may offer additional routes of entry for bacteria (Corrand et al 2012, Andreasen 2013, Du Toit 2014. The game birds industry has experienced tremendous development and expansion during recent years (Tavakkoli et al 2013, Tavakkoli et al 2014a.…”
Section: Introductionmentioning
confidence: 99%